PP.28.25: ASSOCIATION OF 10 GENES POLYMORPHISMS WITH ESSENTIAL HYPERTENSION RISK AMONG A REPRESENTATIVE SAMPLE OF ADULT POPULATION OF PORTUGAL (PHYSA STUDY). (June 2015) - Polonia, J.; Martins, L.; Pinto, F.; Nazare, J.; Bicho, M.
Abstract : Objective: Several single nucleotide polymorphisms (SNP) have been associated with arterial hypertension (HT). Design and method: We investigated in a representative sample of the Portuguese adult population (PHYSA study) the distribution and the association with HT phenotypes of 16 variants of 10 genes that have been considered as susceptibility loci for HT and salt sensitivity. Study subjects comprised 3, 720 individuals (2, 152 normotensives and 1, 568 hypertensives, 394 untreated). The genotypes of SNPs were determined by high-throughput DNA Microchip platform using iPlex MassAssay system from Sequenom. PCR Malditof mass spectrometry. Results: Multivariable logistic regression analysis with adjustment for age, gender, body mass index and smoking status revealed that polymorphisms of gene GRK4_CM025430 encoding G protein-coupled receptor kinase4 and of gene SCL12A3_RS13306673 encoding Na+ Channel/amiloride-sensitive were independent risk factors for HT (P = 0.025, OR = 1.257, 95%CI [1.029–1.535]; P = 0.048, OR = 1.343, [1.076–1.676]; respectively), whereas polymorphism of gene NOS3_CM981388 encoding NO synthase was protective against this condition (P = 0.022, OR = 0.718, 95%CI [0.540–0.953]. Polymorphism of adducin gene, ADD1_CM021240 was independently associated with an increased risk of cardiovascular event (P = 0.016, OR = 1.079, 95%CI [1.007–1.158]). Quantitative trait analysis indicated that the untreated cases with NOS3_CM981388 polymorphisms had vs the population without it a lower systolic blood pressure (SBP) (126.3 + 18.4 vs 129.5 + 16.9 mm Hg, P = 0.021 and a lower diastolic BP (75.8 + 10.3 vs 74.3 + 10.6 mm Hg, P = 0.046) confirming the protective influence of this polymorphism. In contrast, untreated cases with variant polymorphisms of the angiotensinogen gene (AGT_CM920009 and AGT_CM920010) showed vs the population carriers of wild alleles, respectively a higher SBP (128.8 + 17.9 vs 126.3 + 17.4 mm Hg, P = 0.029) and a higher diastolic BP (74.6 + 10.3 vs 73.6 + 10.4 mm Hg, P = 0.023). Conclusions: Our data suggest that for similar age, gender distribution, and 24 h and nighttime BP the values of aortic stiffness, central aortic pressures and wave reflection of subjects with WCHT are more close to those of normotensives than to those of treated HT reinforcing the concept that WCHT may be a much more benign condition than treated true hypertensive patients for similar 24 h and nighttime BP levels.